Expression and characterization of three new glutathione transferases, an epsilon (AcGSTE2-2), Omega (AcGSTO1-1), and Theta (AcGSTT1-1) from anopheles cracens (Diptera: Culicidae), a major thai malaria vector - Wongtrakul J. (2017)
Glutathione transferases (GSTs) (E.C.2.5.1.18) are multifunctional enzymes involved in the detoxification of many exogenous and endogenous compounds. This study aimed to characterize several new GSTs from Anopheles cracens, a major Thai malaria vector formerly known as Anopheles dirus. The three recombinant enzymes obtained were from the epsilon, theta and omega classes. They showed 8093% identity to orthologous An. gambiae GSTs. AcGSTE2-2 possessed peroxidase activity that cannot be detected for the An. gambiae AgGSTE2-2. AcGSTT1-1 had high activity toward several substrates that are specific for mammalian theta class. The AcGSTO1-1 can use 1-chloro-2,4-dinitrobenzene, dichloroacetic acid, and hydroxyethyl disulfide substrates. The enzymes bound but did not metabolize the organophosphate temephos. The epsilon AcGSTE2-2 functioned as a peroxidase and DDT metabolizing enzyme. The theta AcGSTT1-1 functioned not only as peroxidase but also acted as a binding protein for organophosphates. The omega GST had thiol transferase activity suggesting a role in oxidative stress response. © 2010 Entomological Society of America.